The costs and benefits of multistage configuration: A framework and case study. (March 2021) - Bredahl Rasmussen, Jeppe; Haug, Anders; Shafiee, Sara; Hvam, Lars; Henrik Mortensen, Niels; Myrodia, Anna
Highlights: Product configuration systems are typically used to support single processes. A framework for supporting multiple processes (stages) is proposed. Two strategies for multistage product configuration systems are defined. A case study supports the proposed framework. The case shows multistage configuration systems can be profitable. Abstract: Product configuration systems (PCSs) have been successful applications of artificial intelligence principles in engineer-to-order (ETO) companies in recent decades. Such applications mainly focus on quotation or production processes rather than multiple business processes. However, in some cases, there could be a benefit of applying multistage PCSs, that is, PCSs that can support several business processes. To investigate the conditions required for the beneficial application of multistage PCSs, this study examines the costs and the benefits associated with this approach. This is done by outlining a framework that defines multistage configuration, hereunder the identification of costs and benefits, as well as the strategies for implementing the approach. The framework is tested through a case study of an ETO company, which provides empirical evidence of the feasibility and the potential benefits of multistage configuration projects. Specifically, the case study shows that investments are modest when moving from a single-stage configurator strategy to a multistage strategy, while demonstrating significant benefits. This paper thereby provides two novel contributions: (1) a definition of multistage configuration, hereunder two strategies for its implementation and (2) empirical evidence that identifies costs and benefits of multistage product configuration, thereby, supporting its feasibility.